Dynamika zmian sumy i struktury opadów w Wielkopolsce w latach 1981-2020 - Walkowska, Anita; Półrolniczak, Marek; Kolendowicz, Leszek (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
The study analyzes the temporal and spatial variability of atmospheric precipitation and the impact of global climate changes on precipitation in Wielkopolska. The study was based on data provided by the IMGW-PIB and collected from 5 synoptic stations located in central Poland. The average multiannual sums of precipitation, the average number of days with precipitation in total and the particular types of precipitation in 1981–2020 were calculated, and their spatial distribution presented. Moreover, seasonal precipitation totals and statistics for days with precipitation were also calculated, and trends of individual pluviometric characteristics presented. The average annual rainfall was 523 mm, and the average annual rainfall frequency was 163 days. Days with rainfall were more frequent than days with snow (35 days). Over the course of many years, there was an apparent decrease in days with snowfall (-6.5 per decade) and an increase in the number of rainy days (4.3 per decade). Annual precipitation totals show no significant long-term changes.